2012
DOI: 10.1155/2012/528423
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Articular Cartilage Defects in the Knee: Are We Winning?

Abstract: Articular cartilage (AC) injury is a common disorder. Numerous techniques have been employed to repair or regenerate the cartilage defects with varying degrees of success. Three commonly performed techniques include bone marrow stimulation, cartilage repair, and cartilage regeneration. This paper focuses on current level of evidence paying particular attention to cartilage regeneration techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Articular cartilage is devoid of blood vessels and nerves with low presence of chondrocytes with minimum mitotic activity, therefore this particular tissue has little or no potential for healing compared with other tissues. The inability of articular cartilage to regenerate was first reported by Hunter in 1743 ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Articular cartilage is devoid of blood vessels and nerves with low presence of chondrocytes with minimum mitotic activity, therefore this particular tissue has little or no potential for healing compared with other tissues. The inability of articular cartilage to regenerate was first reported by Hunter in 1743 ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…With a limited endogenous ability for self-repair, damaged cartilage as a result of disease or trauma oftentimes leads to premature arthritis. Although current clinical methods are insufficient for long-term treatment [6], tissue engineering strategies provide promising alternatives for cartilage repair. To date, many research groups have adapted a wide variety of natural or synthetic polymers for the fabrication of scaffolds for cartilage tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have demonstrated that the use of bilayer collagen membranes presents an adequate environment for cell attachment and chon drogenic differentiation (Gigante et al, 2007). However, there are no clinical findings that clearly prove the superiority of MACI over existing techniques (Memon and Quinlan, 2012): Indeed, no differences were found in the arthroscopic appearances, histological observations, and rates of tissue hypertrophy between collagen I/III-based ACI-C and bilayer collagen-based MACI grafts used in the treatment of symptomatic cartilage defect cases (Bartlett et al, 2005). MACI is nonetheless an attractive treatment method, as it provides a means of arthroscopic implantation that reduces invasive ness and operation times.…”
Section: Current Treatment Methods For Cartilage Injuriesmentioning
confidence: 99%